Rapid Coating of Aqueous Pearls with Carbon Nanotubes via In Situ Polymerization of Dopamine. (20th August 2021) - Rong, Lin; Mu, Xiaoqing; Zhao, Jinchao; Huang, Leping; Ye, Mingqiao; Wang, Na
Abstract : Millimeter-scale calcium alginate aqueous core capsules (mm-CaSA-Caps) are suitable for embedding of temperature and chemical sensitive substances because of its excellent biocompatibility and biodegradability. In this study, mm-CaSA-Caps were coated with multiwalled carbon nanotubes (MWNTs) via in situ self-polymerization of dopamine (DA) under mild conditions. During the modification process, mm-CaSA-Caps transferred quickly from colorless and transparent capsules to dark and opaque "pearls" in 15 min. The obtained MWNTs-polydopamine- (PDA-) modified mm-CaSA-Caps (mm-MWNTs-PDA@CaSA-Caps) retained the spherical appearance of mm-CaSA-Caps with uniform coating of MWNTs-PDA. Obviously, the MWNTs were easily coated on the mm-PDA@CaSA-Caps due to the strong adhesive property of PDA. As the MWNTs content increased, the stacking density of MWNTs on surface of the mm-MWNTs-PDA@CaSA-Caps raised. The water loss ratio of mm-MWNTs-PDA@CaSA-Caps was enhanced ascribed to increasing the path length of water by raising stacking density of MWNTs. This study provided a new path for enhancement of the barrier property of hydrogel capsules.